Irisin, Angtpl8, Elabela and antioxidants alteration in rats with and without energy drink and treadmill exercise - Pancar, Z.; Cinar, V.; Akbulut, T.; Kuloglu, T.; Sahin, I; Aydin, S. (Verduci Publisher, 2022)
OBJECTIVE: In this study, we sought to investigate the effects of energy drink supplementation and treadmill exercise on the levels of free radicals, antioxidants, Angtpl8, Elabela, and lipid metabolism in rats. MATERIALS AND METHODS: A total of 28 male Wistar albino rats (4 weeks old, 101.96 +/- 9.75g) were included in the study. The rats were randomly divided into four equal groups: control, exercise, supplement, and exercise+supplement groups. At the end of the study, the rats were decapitated, and blood samples were tested for levels of Angptl-8, ghrelin, leptin, irisin, SOD, CAT, TBARS, total oxidant status, and total antioxidant status using enzyme-linked immunosorbent assay. Levels of blood lipids including triglycerides, total cholesterol, HDL-C, and LDL-C were studied using spectrophotometric method in an auto analyzer. RESULTS: Statistical analysis showed statistical significance in TBARS, LDL-C, irisin, Angptl-8, and Elabela levels of the exercise group; SOD and HDL-C levels of the supplement+exercise group; and total cholesterol levels in the supplement group (p < 0.05). Although there were differences between the groups in leptin, ghrelin, and CAT levels, they were not statistically significant (p> 0.05). CONCLUSIONS: As a result, it can be argued that treadmill exercise is important in regulating lipid metabolism and stimulating peptide hormones and receptors. Furthermore, consuming energy drinks without performing exercise or physical activity increases fat stores, and such increases in the critical organs and tissues may pose a threat to the body.
Keywords: Antioxidants; Irisin; Elabela; Exercise; Energy drinks